PENGARUH MODEL PEMBELAJARAN CIRC PADA MATERI KOLOID TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SMA - Kurniati, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe problems of this research were the lack of motivation and the low achievement of students in SMA Negeri 1 Sungai Raya. Purposes of this research were to determine: 1) whether there was a significant difference of achievement beetwen students who were taught using CIRC Cooperative Integrated Reading and Composition model and conventional method on koloid materials, 2) effect size of applying CIRC Cooperative Integrated Reading and Composition model toward achievement on koloid materials, 3) whether there was a significant difference of motivation beetwen students who were taught using CIRC Cooperative Integrated Reading and Composition model and conventional method on koloid materials. Quasi-experimental with nonequivalent control group design was used as research method. The sample were students XI IPA 3 as control class and XI IPA 1 as experimental class that were determined with random sampling technique. Motivations and achievement were analyzed using U-Mann Whitney. The result of data analysis showed that there were significant difference motivations and learning achievement beetwen students who were taught using CIRC Cooperatif Integrated Reading and Composition model and conventional method. CIRC Cooperative Integrated Reading and Composition model gave effect of 43.0% influence on student achievement. Keyword: Cooperative Integrated Reading and Composition, motivations, achievement, koloid materials.